Pengaruh Penggunaan Metode Tikrar Terhadap Kemampuan Menghafal Al-Quran Surah As-Syam Siswa Kelas IV Di SD Islam Cendekia Bukittinggi - Muhammad Adithya; Arifmiboy Arifmiboy; Wedra Aprison; Nurhasnah Nurhasnah (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
This research is motivated by the implementation of tahfidz learning. The memorization method used is not effective so that learning becomes passive, the use of the method is very important in memorizing the Koran because if you don't use the right method it will be difficult when memorizing the Koran. Using an inappropriate method, of course students will feel bored so they have difficulty memorizing. Using the pledge method, making memorization does not only rely on brain memory, but on repeated reading or the term memorization without memorization. Thus, the use of the tikrar method can be used as a solution to overcome the problems of the tahfidz al-Quran learning process. Methods and participants' abilities to memorize the Koran are two variables in this experimental research. This research is directed to determine the differences in students' ability to remember the surah as-Syam using the tikrar method with the conventional method. At SD Islam Cendekia Bukittinggi, the tikrar method has a significant effect on the ability of fourth grade students to memorize the Al Quran, as shown by the results. This is the only result that can be attributed to its application. which yields sig = 0.000, which is less than significant = 0.05, indicating that the TiRAR method has an effect. The average value or effect of the t-test on the sample class obtained from (O2-O1)-(O4-O3) is 20.79, this shows that the pledge method has an effect on memorizing Al Quran Surah As-Syam.